The Role of Emotions and Motivations in Sport Organizations - Tur-Porcar, Ana; Ribeiro-Soriano, Domingo (Frontiers in Psychology, 2020)
In sport organizations, a stance aimed at creating a positive emotional and social climate may be necessary. This study examines athletes’ individual psychosocial factors that are linked to sports practice and sports performance. These factors include individual motivation, emotions, and beliefs. The main objective is to create a hierarchy of emotional and motivational factors that sport organizations can use to increase athletes’ commitment. The Analytic Hierarchy Process (AHP) is used to do so. This method enables analysis of priorities and criteria to support decision-making. The results show that motivation, defined here as the drive that leads individuals to develop plans to achieve their goals by balancing short- and long-term goals, and emotion regulation, defined as the capacity to be aware of and manage one’s emotions to reach a balanced emotional state, are the most important criteria to generate this commitment within sport organizations.